„В некоторых стихиях опознаешь себя” — метафизическая интерпретация материального образа воды в эссе Иосифа Брод¬ского „Набережная неисцелимых” - Nigiel, Adrianna (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
Describing the poetry of Venclova, Brodsky states that „every major poet has an idiosyncratic inner landscape against which his voice sounds in his mind or, if you prefer, subconsciously”[1]. We cannot but look at it as a potentially auto-referential remark. For Brodsky, definitely a major poet, such a place is Venice, yet it is surprising that his chief essay on that place does not capture many scholars’ attention. At the same time, there are relatively few studies that focus exclusively on the poetic images in Brodsky’s works as the material realization the poet’s reverie. That seems to be a huge negligence given that the metaphysical concern so characteristic of the poet is at its peak in this literary piece. The present study focuses on the images of water in Brodsky’s essay as being the chief substance of his cosmic reverie. The methodology derives from Bachelard’s phenomenological method, the aim of which is to communicate with the imagining consciousness of the poet who creates original images specific to him- or herself. While the poet’s experiences are not taken into account in uch an approach, the cosmology they recreate in poetry is and should be. The main aspects of Brodsky’s cosmic reverie communicated through water are that of the inherent connection between the poet and the universe he creates (а „diffuse ontology”), the existential conflict between human life and absolute Time that is a typical motif in Brodsky’s literary work, as well as the transcendental quality of poetry. All the abovementioned supports Bachelard’s intuition and encourages further study of the poet’s work in this context.